CENTRE AND PERIPHERY IN THE EU ECONOMY AT THE CURRENT STAGE OF ENLARGEMENT - Alkhovitska, Olena (Journal of European Economy, 2017)
The article analyses the world system «center-periphery», its concept and principles of interaction among its elements: center, semi-periphery, and periphery. The author studies the stages of EU enlargement from the standpoint of «center-periphery» concept and defines the main tasks of European structural policy in the context of eastern enlargement and prevention of its peripherization.